STRATEGIES FOR SUSTAINABLE COASTAL FISHERY PORT DEVELOPMENT: A CASE OF PASONGSONGAN COASTAL FISHING PORT TECHNICAL SERVICES UNIT, SUMENEP REGENCY, INDONESIA - Subari, Slamet; Zaen, Harun; Sugiarti, Teti; Priyanto, Moh. Wahyudi (LPPM Universitas Trunojoyo Madura, 2024)
The operations of the Coastal Fishing Port Technical Services Unit (Port-TSU henceforth) in Pasongsongan face several challenges that obstruct port activities. First, the anchorage has become more shallow due to the sedimentation resulting from the Angsono River’s erosion. Second, the limited area of the anchoring pool makes it difficult for fishing boats to anchor. Third, the shipping lanes, just like the anchorage, have become more shallow due to sedimentation from the mouth of the Angsono River. Fourth, the limited loading and unloading docks result in long queues, which not only delay ship activities in the queue but also reduce the quality of catches. Fifth, the damaged roads and drainage systems around the port pose a challenge to the loading and unloading activities. Considering these challenges, this research aims to evaluate Port-TSU facilities in Pasongsongan, understand the causes of Angsono River sedimentation, and formulate development strategies for the Port-TSU. The results show that the condition of Port-TSU facilities is generally adequate according to Minister of Maritime Affairs and Fisheries Regulation No. 08 of 2012. However, the rapid erosion of the Angsono watershed caused the shallowing of the anchor pool and shipping lanes. The underlying causes are monoculture farming practices, lack of agroforestry implementation, and the absence of agricultural terracing systems. The development strategy recommendation is to dredge the anchorage and shipping lanes and extend the pier. Other recommendations include implementing watershed management through agroforestry and terracing systems in the Angsono River watershed to minimize erosion and increase loading and unloading capacity by adding a conveyor belt to accelerate processes and reduce ship queues.